Aging well on the autism spectrum: the perspectives of autistic adults and carers. (11th August 2017) - Hwang, Ye In (Jane); Foley, Kitty-Rose; Trollor, Julian N.
ABSTRACT: Background: "Aging well" is an increasingly popular concept in gerontology. Adults with disabilities such as autism spectrum disorder represent a demographically substantial population, yet remain excluded from existing conceptualizations of aging well. This qualitative study aimed to explore what it means for autistic adults to "age well" from the perspectives of autistic adults and carers. Methods: Twenty-four semi-structured interviews were conducted with 15 autistic adults (mean age 50.3 years) and 9 carers of autistic adults. Interviews were offered in four formats: email, telephone, Skype, and face-to-face and included three questions exploring what it means for autistic adults to age well as well as what might help or hinder them from aging well. Results: Aging well was found to be a multifaceted concept that encompassed the autistic individual, others, the world they live in, and relational issues connecting these domains. Thematic analysis revealed eight themes to be common across participants' responses: "myself, " "being autistic, " "others, " "lifestyle and living well, " "being supported, " "relating to others, " "life environment, " and "societal attitudes and acceptance." Conclusions: In line with previous studies, a more diverse range of personal and environmental factors should be included in conceptualizing aging well. In contrast to dominant perspectives, being autistic was not considered a hindrance to aging well. Rather, social and relational issues were central and unique to aging well for autistic adults. Implications include the need to address societal attitudes towards autism and building capacity and understanding in those who are both formally and informally involved in the lives of autistic adults.